A CORRELATION STUDY BETWEEN FREQUENCY OF VIEWING YOUTUBE AND STUDENTS’ LISTENING COMPREHENSION - Sulaiman, Eugelin; Aprianti, Iis; Siahaan, Desta Gloria; Eni, Genoveva Dua (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2022)
The study is about correlational study between the students’ frequency of viewing YouTube English Program and their listening comprehension. The objectives of the study is to find out whether or not a correlation between frequency of viewing YouTube video and their listening comprehension. This study employed quantitative method and is designed to be correlational. In collecting the data, the writer used questionnaire as the proper instrument to find out the students’ frequency of viewing YouTube as the independent variable and their listening comprehension score as the dependent variable. The data were analyzed using SPSS (Statistical Product and Service Solutions). From 30 students, 23% of them view YouTube four to five hours a day, 13% students between three to four hours a day, 40% students two to three hours a day, 17% viewed YouTube one to two hours a day, and 7% of them stated that they had never viewed any YouTube English programs. Most of the English program videos in YouTube that they watch consist of the entertainment and educational programs. From the data analysis of the correlation between students’ frequency of viewing YouTube English program and their listening comprehension, it was found 0.901 (r test= 0.901). This result then was consulted with the r-table in a significant level of 1% with N= 30 is 0.463. The data shows that r value is higher than r- table value (0.901>0.463). It means that the alternative hypothesis (Ha) is accepted while the null hypothesis (Ho) is rejected. In the other words, the result shows that there is a positive correlation between students’ frequency of viewing English YouTube program and their listening skill.